Scalability study of FlowVision on the cluster with Angara interconnect - Akimov, V.S.; Silaev, D.P.; Simonov, A.S.; Semenov, A.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2017)
The scalability of computations in FlowVision CFD software on the Angara-C1 cluster equipped with Angara interconnect is studied. Several test problems with 260 thousand, 5.5 million and 26.8 million computational cells are considered. Computations in FlowVision are performed using a new solver of linear systems based on the algebraic multigrid (AMG) method. It is shown that the special FlowVision’s technology named «Dynamic balancing» significantly improves the performance of computations if the peculiarities of the problem promote the non-uniform loading of CPUs. The Angara-C1 cluster demonstrates the excellent performance and scalability characteristics comparable with its analogues based on the 4х FDR Infiniband interconnect.